2022
DOI: 10.1177/13694332211054229
|View full text |Cite
|
Sign up to set email alerts
|

Flexural behaviour of geopolymer concrete beams reinforced with BFRP and GFRP polymer composites

Abstract: The paper presents the experimental investigations on the flexural behaviour of geopolymer concrete beams reinforced with Basalt Fibre Reinforced Polymer (BFRP)/Glass Fibre Reinforced Polymer (GFRP) rebars and the effect of inclusion of the new adhesively bonded BFRP/GFRP stirrups. M30 grade geopolymer and conventional concrete beams with the dimension of 100 × 160 × 1700 mm were cast to investigae the flexural behaviour of BFRP/GFRP and steel bars. This study also examined the mode of failure, deflection beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Moreover, Cappellesso et al (2023) reviewed the efficiency of self-healing concrete technologies, affirming the potential of microbial and chemical methods to extend the service life of concrete structures (13). The research on Ground Granulated Blast Furnace Slag (GGBS) in concrete by Subramanian et al (2022) also emphasizes the improved flexural behavior and durability of concrete beams reinforced with polymer composites (14). In addition, the investigations into the prediction of self-healing characteristics of concrete with GGBS by M. and the work of Aleem et al on the properties of Geopolymer concrete with M-sand provide comprehensive insights into the advancements in concrete technology that contribute to more sustainable construction practices (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Cappellesso et al (2023) reviewed the efficiency of self-healing concrete technologies, affirming the potential of microbial and chemical methods to extend the service life of concrete structures (13). The research on Ground Granulated Blast Furnace Slag (GGBS) in concrete by Subramanian et al (2022) also emphasizes the improved flexural behavior and durability of concrete beams reinforced with polymer composites (14). In addition, the investigations into the prediction of self-healing characteristics of concrete with GGBS by M. and the work of Aleem et al on the properties of Geopolymer concrete with M-sand provide comprehensive insights into the advancements in concrete technology that contribute to more sustainable construction practices (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Structures made of materials of this type are characterized primarily by such properties as: light weight, high strength, excellent mechanical/fatigue properties, corrosion resistance, etc. The above-mentioned issues, among others, were presented in the papers [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Hadi et al 2022 experimentally investigated the axial load-bending behaviours of BFRP reinforced geopolymer concrete filled BFRP tube columns by applying various load eccentricities and found that GPC-BFRP based specimens were more ductile than normal concretebased specimens. Subramanian et al (2022) experimentally examined the flexural behaviour of geopolymer concrete beam reinforced with BFRP rebars, in terms of failure mode, curvature moment capacity, and crack width, etc. The results showed that BFRP reinforced geopolymer concrete beams demonstrated premature failure and sudden shear failure, compared to conventional steel-reinforced concrete beams.…”
Section: Introductionmentioning
confidence: 99%